YAP: Yield Modeling and Simulation for Advanced Packaging - Chen, Zhichao; Gupta, Puneet (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Three-dimensional integration technologies present a promising path forward for extending Moore's law, facilitating high-density interconnects between chips and supporting multi-tier architectural designs. Cu-Cu hybrid bonding has emerged as a favored technique for the integration of chiplets at high interconnect density. This paper introduces YAP, a yield model for wafer-to-wafer (W2W) and die-to-wafer (D2W) hybrid bonding process. The model accounts for key failure mechanisms that contribute to yield loss, including overlay errors, particle defects, Cu recess variations, excessive wafer surface roughness, and Cu density. We also develop an open-source yield simulator and compare the accuracy of the near-analytical yield model with the simulation results. The results demonstrate that YAP achieves virtually identical accuracy while offering over 10,000x faster runtime. YAP enables the co-optimization of packaging technologies, assembly design rules, and overall design methodologies. We used YAP to examine the impact of bonding pitch, compare W2W and D2W hybrid bonding for varying chiplet sizes, and explore the benefits of tighter process controls, such as improved particle defect density.